The Endangered Central Malay Folklore: A Medium for Internalizing Character Values in Indonesian Language and Literature - Youpika, Fitra; Sumiyadi, Sumiyadi; Permadi, Tedi; Sunendar, Dadang; Yandryati, Jenny (Universitas Negeri Makassar, 2024)
This study raises the unity of the topics of folklore, literature teaching materials, and character education. It aims to explore character education values in endangered Central Malay folklores as a means of internalizing literature teaching. This qualitative study used five informants who not only knew the folklores but also knew the local culture of the Central Malay community in depth. Data were collected through semi-structured interviews and note-taking. The data were analyzed using a thematic approach. The research findings show that Central Malay folklore has aesthetic, humanist, ethical, and religious values that can be internalized in literature learning as a form of effort to save Central Malay folklore from extinction through education. This research is not new. However, there is little information about Central Malay folklore in Indonesia. The findings provide benefits and recommendations to researchers, educators, teachers, and policymakers to collaborate and conduct further studies to save Central Malay folklore from extinction and survive in society. In addition, the importance of this research is to increase understanding and foster students' appreciation of local literature while being able to take and practice the character values contained in Central Malay folklore.